On the colorimetric determination of digitoxin. Application of the colorimetric system of Sols (Revista Española de Fisiología, 1947)
The colorimetric estimation of digitoxin with alkaline picrate is investigated. There is a systematic and inconstant deviation to Beer’s law. For these motives the employ of Sols’ two-standards colorimetry is advisable. With this procedure exact results are obtinable within concentrations comprised between 0.01 and 0.1 0/00.